Time-dependent dual mode of action of COX-2 inhibition on mouse serum corticosterone levels - Pańczyszyn-Trzewik, Patrycja; Sowa-Kućma, Magdalena; Misztak, Paulina; Tabecka-Lonczynska, Anna; Stachowicz, Katarzyna (Steroids, 2024)
•Short-term COX-2 inhibition increased corticosterone levels,•Long-term COX-2 inhibition lowered corticosterone levels,•Corticosterone levels are regulated through a COX-2-dependent mechanism in mice. To elucidate the effect of cyclooxygenase-2 (COX-2) inhibition on corticosterone release, mice were divided into a group receiving NS398, a selective COX-2 inhibitor at a dose of 3 mg/kg for seven days, and a group receiving NS398 for fourteen days. After this time, the mice were sacrificed, and blood serum was collected. An ELISA protocol was used to analyze serum corticosterone levels. Short-term COX-2 inhibition increased corticosterone levels, while long-term inhibition lowered them. The exact schedule of experiments was repeated after the lipopolysaccharide (LPS) Escherichia coli challenge in mice to check the influence of stress stimuli on the tested parameters. In this case, we observed increases in corticosterone levels, significant in a seven-day pattern. These results indicate that corticosterone levels are regulated through a COX-2-dependent mechanism in mice.